MENCEGAH PERUNDUNGAN DI SEKOLAH DASAR DENGAN MENINGKATKAN KOMPETENSI KOMUNIKASI DAN KOLABORASI SISWA - Sartika Yolanda; Yeni Yuniarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Preventing bullying also needs to be done in the school environment, because there are many cases of bullying in schools, this in addition to reducing student motivation to learn also has a long impact on student confidence and the ability to explore their interests and talents, so it is necessary to make several efforts to prevent bullying in schools. The method used to collect data is a literature study by searching for data through several articles. The results obtained are that schools need activities that improve communication skills so that students can inform what they feel, especially in stressful situations. As well as collaboration skills, where students have an empathetic attitude towards their friends who are victims of bullying or the perpetrators to remind each other and prevent bullying from happening.